Genome sequencing unveils a regulatory landscape of platelet reactivity - Ali R. Keramati (Nature Portfolio, 2021)
Platelet aggregation is associated with myocardial infarction and stroke. Here, the authors have conducted a whole genome sequencing association study on platelet aggregation, discovering a locus in RGS18, where enhancer assays suggest an effect on activity of haematopoeitic lineage transcription factors.